Analysis Of Fixed Asset In Indonesia’s Construction Companies Based On International Financial Reporting Standards (IAS 16) Consistent With (PSAK No.16) - Liban Isak Mohamed; Yuniarti Hidayah Suyoso Putra (Syntax Literate, 2022)
The primary purpose of this research study is to thoroughly examine the implementation of Statement of Financial Accounting Standard Number 16 at a construction company in Indonesia, particularly fixed assets, from purchasing fixed assets to disposal of the asset. In almost every company, a fixed asset is considered one of the main valuable factors for the company’s existence to carry on with its daily operations to produce outputs. Without fixed assets, the companies cannot perform in the business cycle, and the significance of fixed assets for the business is immeasurable. Almost publicly-traded entities in Indonesia’s, fixed asset presentation following PSAK No.16. However, the disclosure of fixed assets still does not imply the standard due to the company’s business combination activity. This research is designed based on the qualitative descriptive method. Proven by research, it led to the conclusion that the construction companies like PT. Alam Sutera Realty and PT. Akam Indonesia presents its fixed assets according to the Statement of Financial Accounting Standard number 16